Effect of different ectopic pregnancy treatments on cryopreserved embryo transfer outcomes: A retrospective cohort study - Bingqian Zhang; Lianbao Cao; Lingling Ding; Lei Yan; Zi-Jiang Chen (Wolters Kluwer Medknow Publications, 2017)
Objective: To evaluate the effects of different treatment methods for previous ectopic pregnancies (EP) on cryopreserved embryo transfer (CET) outcomes. Materials and Methods: This was a retrospective cohort study. Patients with EP histories were divided into four groups based on their previous EP treatments: Group 1-unilateral tubal removal; Group 2-bilateral tubal removal or unilateral tubal removal with contralateral tubal ligation; Group 3-conservative surgery group; and Group 4-conservative medication group. A total of 1333 women with previous histories of being admitted to the hospital for CET treatment were consecutively enrolled between January 2009 and December 2014. Results: Patients who underwent bilateral tubal ligation or removal had a lower miscarriage rate [8.88% vs. 3.46%, p=0.006, odds ratio=2.718, 95% confidence interval (CI)=1.301-5.677] than those who underwent unilateral tubal removal. No significant difference was observed in the rate of EP after CET in the four groups in women with EP histories. (p1=0.258, 95%CI=0.113-1.836; p2=0.137, 95%CI=0.975-0.997; p3=0.314, 95%CI=0.987-1.001; p4=0.198, 95%CI=0.987-1.001). The groups were not different with regard to other pregnancy outcomes. Conclusion: There was no significant difference among EP treatment methods with regard to their impacts on CET outcomes in women with EP histories. Bilateral tubal ligation or removal surgery can decrease the miscarriage rate after CET.